KH. HASYIM MUZADI’S EDUCATIONAL MANAGEMENT FOR MEMORIZER 30 JUZ OF AL-QUR’AN - Rosidin; Yuli Salis Hijriyani; Subur Wijaya; Iklil Athroz Arfan (Leadership:Jurnal Mahasiswa Manajemen Pendidikan Islam, 2026)
A crucial problem facing Islam in Indonesia is that those who have memorized Al-Qur’an (hafiz) are not trained to become ulama (Islamic scholars), while ulama do not hold the status of hafiz. KH. Hasyim Muzadi addressed this problem through the educational management at the Sekolah Tinggi Kulliyatul Qur’an (STKQ) Al-Hikam in Depok, which only accepts students who have memorized all Thirty-Juz of Al-Qur’an. This article was written using a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation. The data were then analyzed using the interactive model. The article presents three findings: First, the preservation of the Thirty-Juz Qur’an memorization through three strategies: a) structured review conducted daily, weekly, monthly, and by semester; b) flexible independent review during obligatory prayers, voluntary prayers, and free time; c) assigning first- and second-semester students to lead congregational prayers using the khataman system. Second, the development of Qur’anic knowledge through three programs: a) STKQ Al-Hikam’s intracurricular courses that study disciplines in accordance with Ilmu Al-Qur’an dan Tafsir (IAT) program; b) the Diniyah Ma’had Jami’ah extracurricular program that studies classical Islamic texts (turath); c) organizing academic forums ranging from local to international levels. Third, the practical application of the Qur’an through three activities: a) serving as educators at the Al-Hikam Qur’anic Education Center (TPQ) for children and adolescents; and the Qur’an Reading and Writing Guidance Program (BBTA) for adults and the elderly; b) actively participating in local community activities; c) participating in the Prosakti (Community Service Program) for one year in 3T (Frontier, Remote, and Underdeveloped) areas spread across various provinces in Indonesia. The contribution of this article is to present the best practices of KH. Hasyim’s educational management, which transforms Qur’an memorizers into scholars of the Qur’an. Keywords: Educational Management, Hasyim Muzadi, Memorization of Qur’an, STKQ Al-Hikam, Tahfiz al-Qur’an.   Abstrak Problem krusial Islam di Indonesia adalah penghafal Al-Qur’an (hafizh) tidak dibina menjadi ulama, sedangkan ulama tidak berstatus hafizh. Problem ini diberikan solusi oleh KH. Hasyim Muzadi melalui manajemen pendidikan di Sekolah Tinggi Kulliyatul Qur’an (STKQ) Al-Hikam Depok yang hanya menerima hafizh 30 Juz sebagai mahasiswa. Artikel ini disusun menggunakan pendekatan kualitatif, jenis studi kasus dan desain penelitian lapangan. Data diperoleh melalui observasi, wawancara dan dokumentasi. Lalu dianalisis dengan model interaktif Miles, Huberman dan Saldana. Ada tiga temuan artikel: Pertama, pelestarian hafalan Al-Qur’an 30 Juz melalui tiga strategi: a) muraja’ah terstruktur yang bersifat harian, mingguan, bulanan dan semester; b) muraja’ah mandiri secara fleksibel dalam shalat fardhu, shalat sunah dan jam kosong; c) penugasan sebagai imam shalat jamaah bagi mahasiswa semester satu dan dua dengan sistem khataman. Kedua, pengembangan wawasan Al-Qur’an melalui tiga program: a) perkuliahan intrakurikuler STKQ Al-Hikam yang mempelajari disiplin ilmu sesuai Program Studi Ilmu Al-Qur’an dan Tafsir (IAT); b) program ekstrakurikuler Diniyah Ma’had Jami’ah yang mempelajari kitab kuning (turats); c) penyelenggaraan forum ilmiah berskala lokal hingga internasional. Ketiga, praktik Al-Qur’an melalui tiga kegiatan: a) menjadi pendidik di Taman Pendidikan Al-Qur’an (TPQ) Al-Hikam untuk anak-anak dan remaja; serta Bimbingan Baca Tulis Al-Qur’an (BBTA) untuk orang dewasa dan lansia; b) menjadi peserta aktif dalam kegiatan masyarakat sekitar; c) menjadi peserta dalam Prosakti (Program Masa Bakti) selama satu tahun di daerah 3T (Terdepan, Terpencil dan Tertinggal) yang tersebar di berbagai provinsi di Indonesia. Kontribusi artikel ini adalah menyajikan best practice manajemen pendidikan KH. Hasyim yang memproses hafiz Al-Qur’an menjadi ulama ahli Al-Qur’an. Kata Kunci: Hafalan Al-Qur’an, Hasyim Muzadi, Manajemen Pendidikan, STKQ Al-Hikam, Tahfiz Al-Qur’an.